Non-enhancing intraventricular tumours in adults - Mujtaba Khalil; Saqib Kamran Bakhshi; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2022)
Intraventricular tumours are relatively uncommon among all brain tumours, and non-enhancing lesions, mostly subependymoma, are even less frequently reported. Select cases of subependymoma can show variable contrast enhancement as well. Gross total surgical resection is recommended for treating these lesions, with no significant role of adjuvant chemotherapy or radiotherapy. Keywords: Intraventricular tumors, Subependymoma, Non-enhancing lesions.